Harvard Square a love story - Turco, Catherine J. ca. 20. Jh (Columbia University Press, 2023)
"As Catherine Turco found herself stepping to the microphone at a public hearing in a basement to admonish the representative for Equity One, the new owner of a set of commercial buildings on Brattle Street, which planned to evict all of the existing tenants and redevelop the property, she realized she had a problem. Why was an MIT business professor and former investment banker getting emotional about the fate of a bunch of stores she never shops in? Who cares what some bank does with its property? Well, she did, and so did everyone else at the meeting, but why? Written by a longtime denizen of the Square, Harvard Square explains why people become so passionately attached to their local downtown markets and why it always seems like it used to be better before.
Keywords: Harvard Square (Cambridge, Mass.); Central business districts / Massachusetts / Cambridge; Central business districts; Massachusetts / Cambridge; Massachusetts / Cambridge / Harvard Square